SIMULATION OF GEOMETRIC ATTACKS AGAINST TRANSMISSION SYSTEMS OF THE HIDDEN INFORMATION - Шматок, А. С.; Петренко, А. Б.; Єлізаров, А. Б.; Панадій, В. С. (Science-based technologies, 2015)
An actual objective is justified, and tasked by to development algorithm of the software, which will performgeometric attack on the container, as amended by LSB him hidden information. The aim of the task was to developan automatic mechanism to destruct hidden information in a graphical container through geometric to allposted users resources of the channels. As a result, to protect the system from malicious code and protectagainst leaks of confidential information hidden by methods of steganography, steganalyst no longer have tocheck every container. Through affinity attacks, the system will provide protection by itself, thereby significantlyreducing the amount of time, and due to continuing increase in productivity of automated systems, processingperformance of the mechanism will increase.